Estratégias mercadológicas utilizadas pelo Banrisul para captação e retenção de clientes do público jovem através de seus meios digitais - Miotto, Cícero Antônio (2023)
By adopting marketing strategies to attract and retain young customers, Banrisul targets several aspects that are fundamental to its long-term sustainability and relevance. Considering that young customers represent the future of any financial institution's clientele. By attracting and winning over this audience, constant renewal of its base is ensured, guaranteeing the continuity and vitality of its operations. The adoption of marketing strategies aimed at young people is a proactive and necessary approach to remain relevant, sustainable and aligned with the constantly evolving demands of the financial market. This work's main objective is to explore the marketing strategies adopted by Banrisul with a focus on attracting and retaining young customers. We sought to understand how the bank's actions were received by the target audience and analyze the effectiveness of these strategies in a scenario marked by rapid digital transformation and the growing demands of younger generations. To achieve this objective, a survey was carried out that involved the application of a questionnaire to a representative sample of young Banrisul customers. Quantitative and qualitative methods were used to collect and analyze data, including structured questions about brand perception, banking preferences, expectations regarding products and services, among others. The results obtained revealed important information about the young public's perception of Banrisul. A positive association was observed between perceived security at the bank and preference for its services. This study contributes significantly by providing an in-depth analysis of Banrisul's marketing strategies aimed at young people. The findings offer valuable input to improve the bank's approach, highlighting specific areas that require adjustments to better meet the expectations and needs of this crucial market segment.